2011
DOI: 10.1589/jpts.23.845
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness and Metabolic Markers in Healthy Young Adult Men

Abstract: Abstract.[Purpose] The purpose of this study was to clarify the relationship between cardiorespiratory fitness and metabolic markers, including leptin, in healthy young adults.[Subjects] The subjects were 51 healthy young men (mean age, 21.6 years; range, 18-31 years).[Methods] Ventilatory threshold and maximal oxygen uptake were measured on a cycle ergometer. The metabolic markers, HDL-cholesterol, triglyceride, fasting glucose, fasting insulin and leptin, were also measured, as well as and body composition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…In addition, no subject in this study had a relationship between aerobic capacity and FFM and BMI. This is supported by the study of Yagura et al 15 ) . This may indicate that aerobic capacity was not influenced by skeletal muscle mass but rather by lipid profiles among the middle-aged normolipidemic and dyslipidemic Thai participants in this study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, no subject in this study had a relationship between aerobic capacity and FFM and BMI. This is supported by the study of Yagura et al 15 ) . This may indicate that aerobic capacity was not influenced by skeletal muscle mass but rather by lipid profiles among the middle-aged normolipidemic and dyslipidemic Thai participants in this study.…”
Section: Discussionsupporting
confidence: 71%
“…Both mechanisms decrease oxygen transport capacity of the vasculature, either at the peripheral vasculature or by centrally affecting the heart 10 ) . Thus, aerobic capacity or maximal oxygen consumption (VO 2, max ) is normally used to determine cardiorespiratory fitness 11 , 12 , 13 , 14 , 15 ) . A low VO 2, max is associated with CVD risk factors (i.e., lipid profiles 16 ) ) such as obesity 17 , 18 ) and hypertension 19 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of physical fitness are related to its reduction of the risk of cardiovascular dysfunction and to the delayed onset of metabolic syndrome activity of the proteins involved in insulin signal transduction in skeletal muscles 17 , 18 , 19 ) . Therefore, by following a systematic exercise program, PCOS patients can improve their cardiopulmonary functional capacity and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to sustain high metabolic power for long periods is very important for athletes competing in triathlons. Several field-based studies have shown that physiological and morphological functional characteristics change negatively with age 2 , 3 ) . It is very important that triathletes have suitable anthropometric and physiological characteristics to advance performance in the three disciplines involved.…”
Section: Introductionmentioning
confidence: 99%